Daylength effects on black spruce bud dormancy release change during endo- and ecodormancy - Colombo, Stephen J.; Man, Rongzhou (Frontiers in Forests and Global Change, 2023)
The effects of daylength on bud dormancy release varied throughout the dormant period in black spruce (Picea mariana (Mill.) B.S.P.) seedlings. In phase one of this trial, seedlings exposed to 8 h photoperiods to induce terminal buds were then intermittently transferred to 12, 16, 18 or 24 h photoperiods to determine dormancy status, evaluated by observing rates of terminal budburst. Buds were in a state of endodormancy initially after short-day induction, as indicated by their inability to quickly break bud when placed in longer daylengths. The time required for budburst decreased as time after bud initiation increased. Time to terminal budburst also decreased linearly with longer photoperiods. In phase two of the investigation, beginning 9 weeks after terminal bud initiation, seedlings began receiving chilling at +5°C to promote the transition from endo- to ecodormancy. During chilling, groups of seedlings were periodically removed from the cold and placed into warm temperatures at 8, 12, 16, 18 or 24 h photoperiods to observe the rate of budburst. Time to budburst in an 8 h photoperiod decreased logarithmically with the duration of chilling, decreasing more rapidly over the first four weeks of chilling and thereafter more slowly. Photoperiod always affected the rates of budburst: with eight weeks of chilling, longer photoperiods resulted in faster rates of budburst; in contrast, after 16 weeks of chilling, budburst was faster in shorter photoperiods. These results are of practical significance in tree nurseries where controlling bud dormancy release is important. In addition, this trial provides empirical observations of bud dormancy release that contribute to the understanding of environmental control of this aspect of the tree developmental cycle, which may affect tree phenology as the climate changes.